DECORATIVE FINISHING OF MEN’S COSTUME IN THE COLLECTIONS OF DESIGNERS OF THE BEGINNING XXI CENTURY - Лю, Цзянсінь; Пашкевич, К. Л.; Костогриз, Ю. О.; Сербін, О. І. (Art and Design, 2021)
The aim is to explore the decoration of men’s suits in the collections of Ukrainian and foreign designers of the XXI century. Methodology. Applied methods of comparison, visual-analytical, retrospective and artistic-compositional analysis. Results. The varieties of decorative finishing of men’s suits, which were used by designers of Ukrainian and world brands of fashionable clothes in their collections at the beginning of the XXI century, have been studied. The main directions of development of menswear decoration, its main tendencies are determined; artistic means of decorating men’s suits were found in the collections of the World Fashion Houses and in the works of Ukrainian designers. It is established that cardinal changes in the design of men’s clothing began at the beginning of the XXI century, and until now the men’s suit was characterized by the constancy of the general geometric shape and the main compositional solution. During this period, the dynamics of the decorative finishing of men’s suits, which became more diverse and unusual, and often repeated the decoration of women’s suits by color, the use of embroidery with different materials (beads, sequins, quilting, etc.), lace, use of fabrics of different colors, textures, patterns, prints, etc. The scientific noveltyis to determine the dynamics and trends in the decorative finishing of men’s suits in the collections of the World Fashion Houses and Ukrainian designers, which were demonstrated at the beginning of the XXI century. Practical significance. The processed information and materials allowed to determine the leading techniques and types of decorative finishing of men’s suits of the XXI century. The results can be used in further research on the history of fashion and menswear design.